دراسة التحليل المقارنة عقد المضاربة من منظور فتوى المحكمة العليا وفتوى مجلس الشرعي الوطني : An Analysis of Mudarabah Contracts in The Perspective of The Supreme Court Regulation and DSN-MUI Fatwa - Ibrahim, Siti Nawal; Saifullah, Saifullah (Universitas Muhammadiyah Surakarta, 2025)
The purpose of this study is to analyse how the method of sharia contracts in Supreme Court Regulation No. 2 of 2008 concerning the Compilation of Sharia Economic Law (KHES) is compared with the DSN MUI fatwa. To find out the differences and similarities in the application of sharia contract methods between KHES in Supreme Court Regulation No. 2 of 2008 and the DSN MUI fatwa. The scope of research in this research is descriptive, and the approach in this research is a comparative approach and a statutory approach. The analysis used in this research is inductive analysis. The result of this research is in order to compare the method of interpretation of sharia contracts, Supreme Court Regulation No. 100 of Law No. 2 of 2008 concerning the Compilation of Sharia Economic Law (KHES) and DSN-MUI fatwa have different approaches in the implementation of Mudharabah contracts. KHES focuses more on the principle of legal clarity and the initial intention of the parties, because the contract must be made and implemented in accordance with the initial agreed objectives. The interpretation in KHES is more legalistic, so it serves as a court guideline in resolving legal disputes that prioritize clarity, justice and understanding between investors and fund managers. Meanwhile, DSN-MUI Fatwa No. 115/DSN-MUI/IX/2017 tends to use a more flexible jurisprudential approach. This fatwa provides specific guidelines for various forms of Mudharabah contracts such as limited Mudharabah and absolute Mudharabah, making it easier to apply in Islamic financial institutions according to different business contexts. The principles also include transparency and flexibility in capital management, profit sharing and risk responsibility. The similarities of these two directives include a strong foundation in Shariah principles, particularly with regard to transparency, fairness and agreement in principle on the profit ratio. In addition, both KHES and Fatwa DSN-MUI agree that the risk of loss is borne by the investor, unless there is negligence on the part of the fund manager. On the other hand, differences arise in the technical details, where KHES demands clarity and more strictly limits contractual roles, while Fatwa DSN MUI allows variations in the form of capital and provides greater flexibility in the division of roles and profit sharing. Thus, KHES is more important as a legal reference in court, while the DSN-MUI fatwa plays an important role in the operational practices of Sharia financial institutions, which need guidance in managing fair and Sharia-compliant business cooperation.